2015
DOI: 10.3892/ijmm.2015.2302
|View full text |Cite
|
Sign up to set email alerts
|

miR-485-5p inhibits bladder cancer metastasis by targeting HMGA2

Abstract: MicroRNA (miRNA or miR)‑485 is a functional miRNA which has received much attention in recent years. However, little is known about the expression of miR‑485 or the role it plays in bladder cancer [namely in metastasis and epithelial‑mesenchymal transition (EMT)]. Thus, in the present study, we aimed to detect the expression of miR‑485 in human bladder cancer tissues and bladder cancer cell lines, and to examine the effects of miR‑485‑5p on bladder cancer cell metastasis and EMT. We found that the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 30 publications
3
39
0
Order By: Relevance
“…As reported previously, miR-145-3p and miR-505-3p (Yamamoto et al 2011;Matsushita et al 2016) as well as miR-410-3p and miR-485-5p (Shiah et al 2014;Chen et al 2015;Mussnich et al 2015) are downregulated in tumor tissues from different cancers and appear to function as tumor suppressor genes. Consistent with these reports, the pathway enrichment analysis in this study showed that miR-145-3p, miR-299-3p (F-CAFs vs. NFs) and miR-410-3p (F-CAFs vs. In-CAFs) were significantly associated with "pathways in cancer", whereas miR-505-3p (F-CAFs p value of ≤ 0.05 was used to select significant pathways.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As reported previously, miR-145-3p and miR-505-3p (Yamamoto et al 2011;Matsushita et al 2016) as well as miR-410-3p and miR-485-5p (Shiah et al 2014;Chen et al 2015;Mussnich et al 2015) are downregulated in tumor tissues from different cancers and appear to function as tumor suppressor genes. Consistent with these reports, the pathway enrichment analysis in this study showed that miR-145-3p, miR-299-3p (F-CAFs vs. NFs) and miR-410-3p (F-CAFs vs. In-CAFs) were significantly associated with "pathways in cancer", whereas miR-505-3p (F-CAFs p value of ≤ 0.05 was used to select significant pathways.…”
Section: Discussionsupporting
confidence: 77%
“…Next, we selected ten different candidate miRNAs for RT-qPCR validation of the microarray results using matched F-CAFs, In-CAFs and NFs (triplets) from twelve patients diagnosed with primary lung adenocarcinoma. We chose these candidate miRNAs from the microarray results because these miRNAs exhibited the largest fold change or/ and were associated with previously published evidence of relationships with tumors (Yamamoto et al 2011;Shiah et al 2014;Chen et al 2015;Guo et al 2015a;Guo et al 2015b;Mussnich et al 2015;He et al 2016;Matsushita et al 2016). The selected candidate miRNAs were miR- 145-3p, miR-299-3p, and miR-505-5p (downregulated in F-CAFs vs. NFs); miR-6875-3p and miR-6735-5p (upregulated in F-CAFs vs. NFs); miR-181c-5p, miR-5006-5p, and miR-6867-5p (downregulated in In-CAFs vs. NFs); miR-410-3p and miR-485-5p (downregulated in F-CAFs vs. In-CAFs); and miR-6875-3p and miR-6735-5p (upregulated in F-CAFs vs. In-CAFs) ( Table 1).…”
Section: Identification Of Differentially Expressed Mirnas In Cafsmentioning
confidence: 99%
“…In contrast, we find increased HMGA2 by immunohistochemistry and western blot in 70 percent of GBM, suggesting that multiple factors may regulate HMGA2. In other tumor types, HMGA2 levels are controlled by Transforming Growth Factor-β (TGF-β) [34], Raf-1 kinase inhibitory protein [66-68], RUNX1 [37], and several microRNAs [35, 39, 69-73]. …”
Section: Discussionmentioning
confidence: 99%
“…It achieves this by acting as a ceRNA for miR-145, which (a) directly inhibits ZEB2; and (b) indirectly inhibits ZEB1 via targeting Oct4, a transcriptional activator of ZEB1 [185]. UCA1 has also been shown to suppress metastasis of epithelial ovarian cancer by functioning as a ceRNA for miR-485-5p [188], a miRNA which blocks EMT and metastasis through its targeting of MMP14 and HMGA2 [188,300]. UCA1 has also been shown to regulate EMT in Gastric Cancer as, silencing of UCA1 resulted in decreased levels of vimentin and snail, with concomitant elevated levels of E-cadherin [196].…”
Section: Lncrnas and Emt: The Main Playersmentioning
confidence: 99%